A prospective study on comparison of cervical length measured transvaginally and bishop score in predicting successful labour induction - Balaji, T. E.; S., Vijaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Induction of labour is one of the common interventions in obstetric practice. Cervical assessment has been used as a prediction of the successful vaginal delivery. This study is designed to investigate transvaginal ultrasonographic cervical measurement as a predictor of duration of labour and successful induction resulting in vaginal delivery and compare the performance of ultrasonographic cervical measurement with that of the Bishop score in predicting the outcome of labour induction. Methods: It is a prospective observational study. In this study, for the 100 primigravida women with gestational age of 37-42 weeks of gestation admitted for induction of labour, the cervical length was measured by transvaginal ultrasound and then Bishop Score was assessed by digital examination. Predictive values for successful labour induction were detected and compared. Results: Using Spearman’s rho correlation both TVS cervical length and Bishop score have significant correlation in predicting the success of induction of labour. Cervical length is the better predictor of the likelihood of delivering vaginally within 24hrs. In the receiver operating characteristic curves, the best cut-off points for the prediction of successful induction was 26mm for cervical length and 4 for the Bishop Score. However, TVS cervical length appears to be a better predictor than the Bishop Score, with a sensitivity of 58.1% and a specificity of 100% compared to 70.3% and 45.5% respectively. Conclusions: Transvaginal sonographic measurement of cervical length is a better predictor of the likelihood of successful induction of labour within 24hrs of induction and increased vaginal deliveries within 48 hours of induction when compared to Bishop Score.